New selection algorithm for Mengubah Destini Anak Bangsa (MDAB) students / Zamali Tarmudi ... [et al.] - Tarmudi, Zamali; Saibin, Tammie Christy; Naharu, Nasrah; Ung, Ling Ling (2014)
This research introduces a new algorithm to select students from low income family the so-called Mengubah Destini Anak Bangsa (MDAB) using fuzzy approach. It focuses on the refinement and modification of certain variables in selection process. The technique employs the intersection of fuzzy goals and constraints concept in judgmental process. The initial input was directly obtained based on the multi-person opinion and experiences. A numerical example which is related to Universiti Teknologi MARA (UiTM) MDAB students' selection was presented to demonstrate the applicability of the proposed method. It was found that the method has successfully helped in dealing with situations which are relevant to the concern of the university, thus can facilitate the DMs to make a decision in a simple and systematic manner. Finally, our new proposed algorithm and modification of the variables can derive more precise in terms of representing the actual situation.